Enhanced detection of nitrite ions over copper oxide/polymeric carbon nitride composites - Jasman, Siti Maryam (2015)
Nitrogen containing organic compounds such as nitrite ions (NO2-) may cause contaminations to the environment, food and drinking water, which are harmful to human health. In this study, a novel fluorescence sensor was developed by modification of polymeric carbon nitride (CN) with copper oxide (CuO). The polymeric CN was prepared by using urea as a precursor via thermal polymerization techniques, while CuO was introduced onto the polymeric CN via an impregnation method, followed by calcination at 573 K. The formation of the polymeric CN can be confirmed from the Fourier transform infrared (FTIR), where the presence of graphitic structure of heterocyclic tri-s-triazine ring was observed at 809 and 1200-1700 cm-1. The diffuse reflectance ultraviolet visible (DR UV-Vis) spectrum showed the characteristic light absorption of the polymeric CN up to 450 nm. From fluorescence spectroscopy, it was revealed that the polymeric CN exhibited three excitation peaks at 277, 317, and 369 nm owing to the presence of C=N, C=O, and C-N groups, respectively. On the other hand, there was only one emission peak observed at 455 nm. The emission intensity was found to decrease with the increase of CuO loading, suggesting the certain interactions between the polymeric CN and the added CuO. The performances of polymeric CN and CuO/CN composites as fluorescence sensors were evaluated for NO2- with concentration range of 0.5-4 ìM. The quenching rate towards NO2- can be determined from the linear Stern-Volmer plots. It was revealed that the C=N sites in the polymeric CN were the most favored quenching sites for the NO2-. With the optimum addition of CuO (0.1 mol%), the quenching rate for C=N sites was enhanced 2.5 times higher than that of the polymeric CN. This study demonstrated that CuO/CN composite is a promising fluorescence sensor for the detection of NO2.